Adapting AJ Investment New Zealand’s Pasture, Hygiene, and Animal Health Management as a Blueprint for Optimizing Milk Quality in Indonesia - Dewi, Sari Putri; Hakim, Rizal (Unpad Press, 2026)
The high volume of milk imports in Indonesia, reaching 28,280.61 tons per month, necessitates a systematic transformation of the domestic production sector. This study aims to analyze the implementation of pasture-based management at AJ Investment Dairy Farm, New Zealand, to be formulated as a strategic blueprint for optimizing milk quality in Indonesia. Using a descriptive-qualitative approach with an observational design, the research evaluated the holistic integration of nutrition, milking hygiene, and animal health maintenance. The results indicated that a planned paddock rotation system with 93% feed self-sufficiency produced a total of 219,827 kgMS, averaging 379 kgMS per cow and 1,010 kgMS per hectare. Consistency in milk solids (fat and protein) was supported by stable Body Condition Scores within the ideal 4-6 range and a low health disorder incidence of ±2%. Disciplined hygiene, focusing on machine sanitation and multi-stage filtration, effectively maintained microbiological quality within safe limits despite the absence of teat dipping. In conclusion, the synergy of pasture management, hygiene, and animal health is the key to sustainable production efficiency. This model is recommended as a strategic blueprint for Indonesian dairy farming through four main pillars: land valuation, tropical nutrition optimization, managed grazing, and integrated technical indicator evaluation to strengthen national milk self-sufficiency.Keywords: animal health, dairy cattle, milking hygiene, milk solids, pasture management.